PENINDAKAN MINUMAN MENGANDUNG ETIL ALKOHOL BERDASARKAN UNDANG-UNDANG NOMOR 39 TAHUN 2007 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 1995 TENTANG CUKAI OLEH KANTOR WILAYAH DIREKTORAT JENDERAL BEA DAN CUKAI RIAU DAN SUMATERA BARAT - Rachmat Wahyu; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Violatian of beverages contraining ethyl alcohol from year to year has incrased which ultimately hurt the future generation. Along with the development of technology and information, emerging new types of alcoholic beverages. Law enforcement in a broad sense includes activities to implement and apply the law and to take legal action against any breaches or violations of the law. In this case of beverages containing ethyl alcohol is cleary the goods subject to excise, excise levies contries whose main funcation eradicate the circulation of goods subject subject to excise. As referred to in law no 39 of 2007 amendments to the law number 11 of 1995 on excise duty and the presidential decree number 49 of 2009 on the procedures for enforcement in the field of customs.So this research is sociological, because in this study the authors look at in terms of the correlation between law and society, so as to reveal the effectiveness of the rule of law in society and indentifying the unwritten law that applies to the public, so in this study the authors used data types in the the thesis is a qualitative and quantitative, while the types of data sources are primary data and secondary data.From the analysis of the problems that can be concluded rampant cases such as counterfeiting excise stamps, beverages containing ethyl alcohol has an obligation to investigators (PPNS) civil servants and excise duties in revealing and prosecuting those responsible for the suspected person or legal entity who violates the criminal provisions in the field of customs. This study aims to determine the role of civil servant investigators (PPNS) customs in dealing with the prosecution of beverages containing ethyl alcohol and any factors that impede investigators civil servants (PPNS) customs in dealing with the prosecution of beverages containing ethyl alcohol. Pebelitian results can be concluded that, over the development period and the disruption of internasional trade experience barriers to the smooth running of state revenues, especially for developing countries like indeonesia country, because often the occurrence of a crime in the delivery of goods and importation of goods to a certain country. For it as afunction of investigator civil servants (PPNS) customs dab excise run optimally on enforcement violations in the process of criminal investigations in the field of customs and has improved the image of the directorate general of customs and excise provide a sense of justice in the eyes of the general public on the performance conducted in accordance with the mandate of the law on excise.Keywords : Action-Alcoholic Beverages-Laws